Tyr-716 in the platelet-derived growth factor beta-receptor kinase insert is involved in GRB2 binding and Ras activation. - Arvidsson, A K (1994)
Ligand stimulation of the platelet-derived growth factor (PDGF) beta-receptor leads to activation of its intrinsic tyrosine kinase and autophosphorylation of the intracellular part of the receptor. The autophosphorylated tyrosine residues mediate interactions with downstream signal transduction molecules and thereby initiate different signalling pathways. A pathway leading to activation of the GTP-binding protein Ras involves the adaptor molecule GRB2. Here we show that Tyr-716, a novel autophosphorylation site in the PDGF beta-receptor kinase insert, mediates direct binding of GRB2 in vitro and in vivo. In a panel of mutant PDGF beta-receptors, in which Tyr-716 and the previously known autophosphorylation sites were individually mutated, only PDGFR beta Y716F failed to bind GRB2. Furthermore, a synthetic phosphorylated peptide containing Tyr-716 bound GRB2, and this peptide specifically interrupted the interaction between GRB2 and the wild-type receptor. In addition, the Y716(P) peptide significantly decreased the amount of GTP bound to Ras in response to PDGF in permeabilized fibroblasts as well as in porcine aortic endothelial cells expressing transfected PDGF beta-receptors. The mutant PDGFR beta Y716F still mediated activation of mitogen-activated protein kinases and an increased DNA synthesis in response to PDGF, indicating that multiple signal transduction pathways transduce mitogenic signals from the activated PDGF beta-receptor.